New Facile Synthesis of 2-Alkylthiopyrimidin-4(3H)-ones by Tandem Aza-Wittig Reaction Starting from the Baylis–Hillman Adducts - Xiong, Jun; Wei, Xiao; Ding, Ming-Wu (Synlett, 2017)
Iminophosphoranes reacted with CS2 at –5 °C to produce the isothiocyanates, which were treated with primary amine to give thioureas in 73–91% yields. The subsequent reaction of thioureas with alkyl bromides in the presence of solid K2CO3 produced 2-alkylthiopyrimidin-4(3H)-ones in 68–88% yield via tandem intramolecular cyclization–isomerization–S-alkylation.
Keywords: pyrimidin-4(3H)-one; Baylis–Hillman reaction; aza-Wittig reaction; isothiocyanate; isomerization